Emerging arboviral encephalitis. Newsworthy in the West but much more common in the East. - Cardosa, Mary Jane; Solomon, Tom (British Medical Journal, 2000)
The changing epidemiology of West Nile virus (WNV) and Japanese encephalitis virus (JEV) is tackled, with specific emphasis on the prevalence of WNV infection in the USA and Romania and JEV infection in Asia. The clinical presentation, transmission and control of WNV and JEV in the human population are briefly discussed.